STRATEGI PEMASARAN TELUR AYAM RAS DI KABUPATEN KEDIRI - Chamim Rosyidin; Sumarji Sumarji; Ahsin Daroini (Universitas Islam Kadiri, 2019)
ABSTRACT This study aims to determine the distribution channel, analyze the factors of strength, weakness, opportunity and threat in marketing eggs and formulate a marketing strategy used in laying hens in Kediri Regency. The number of samples taken were 30 samples consisting of 15 breeders and 15 breeders who took eggs in the Kediri district. Sampling was by purposive sampling, which was purposely chosen based on certain criteria determined by the researcher, for analysis of the data itself using SWOT analysis and continued QSPM analysis. Based on the results of the study, it is known that the distribution channel for marketing chicken eggs in Kediri Regency is: (Pattern 1 = Farmer → Wholesaler (Poultry Shop) → Medium Merchant → Retailer → Consumer), (Pattern 2 = Farmer → Medium Merchant → Retailer → Consumers) and (Pattern 3 = Farmers → Retailers → Consumers). An alternative strategy that is appropriate for marketing chicken eggs in Kediri district is by using a strategy (ST) that is using internal power to overcome external threats so that the threat will not have too much negative impact by maintaining and maintaining the quality of eggs produced and increasing production through prevention of chicken disease so that livestock businesses can be sustainable. The strategies that need to be implemented first by the farm while maintaining and maintaining the quality of the eggs produced. Keywords: Marketing Strategies, Eggs, Laying Hens, SWOT Analysis.